Workplace Internet Leisure and Employee Productivity: Mediating Role of Employee Engagement - KAUSAR, NAVEEDA; ASHRAF, SHAGUFTA; KHAN, DR. MUHAMMAD MAROOF; KHAN, DR. MUHAMMAD MUDASSAR; MEHMOOD, SHAHID (The journal of contemporary issues in business and government, 2021)
There is an ongoing discussion on the role of workplace internet leisure (WIL) and whether it is a vice or virtue. Considering this, Current study is aimed to examine the effects of Workplace internet leisure on employee productivity with mediating role of employee engagement in the Army health care sector of Pakistan. The data was collected through self-administered questionnaires from Armed forces nursing officers of different Army hospitals and institutes through convenience sampling size of 300.SPSS model macro Version 3 (Hayes, 2018) was used to analyze the respondents’ feedback. For analysis of workplace internet leisure influence on employee engagement regression is calculated and results indicates that workplace internet leisure has positive and significance impact on employee engagement, while work place internet leisure has positive but insignificance impacts on employee productivity. Additionally, indirect analysis is calculated for mediation analysis, results indicate that employee engagement positively mediates association between workplace internet leisure and employees productivity. Keywords: Workplace internet leisure (WIL), Employee productivity (EP), Employee engagement (EE), Self-determination theory(SDT), Job demand-resource model (JDR)